The construction of local identities in Korat, Thailand - Korff, Rudiger (Universiti Kebangsaan Malaysia, 1999)
The invention of local identities is becoming an important issue in many parts of the world. Depending on the given circumstances, localism can turn violent as separatist movements, ethnic rioting, civil war, unrest or other forms. However in Thailand we can notice a different pattern: the creation of local traditions is a crucial aspect of national integration beyond Bangkok. In this article, the city of Korat in Northeast Thailand is taken as a case study, to indicate how local identities are formed through the revitalization of local traditions and customs. Korat turned into a boom town with increased global integration during the late eighties. This in turn made the region attractive for Bangkok-based strategic groups. To be able to compete with this, the local elite had to achieve social cohesion, which was based on local identity. Surprising as it may seem, the case of Korat indicates that globalisation of the political system in Thailand, this local identity becomes the basis for real national integration.